1983
DOI: 10.1083/jcb.96.3.920
|View full text |Cite
|
Sign up to set email alerts
|

Laminin is produced by early rat astrocytes in primary culture.

Abstract: The production of laminin by early rat astrocytes in primary culture was investigated by double immunoffuorescence staining for laminin and the gliat fibrillary acidic protein (GFAP), a defined astrocyte marker. In early cultures (3 d in vitro; 3 DIV) cytoplasmic laminin was detected in all the GFAP-positive cells which formed the major population (80%) of the nonneuronal cells present in cultures from 20-21-d embryonic, newborn, or 5-d-old rat brains. Monensin treatment (10 #M, 4 h) resulted in accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
1
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(139 citation statements)
references
References 47 publications
10
127
1
1
Order By: Relevance
“…In the olfactory system, astrocytic function may include tissue remodeling associated with mitosis and migration of other cells. Astrocyte production of laminin and other extracellular matrix components such as tenascin-C and chondroitin sulfate has been demonstrated under both normal and pathological conditions (29,37). To add further levels of complexity and diversity, there appear to be multiple subsets of GFAP-expressing astrocytes in the olfactory system, distinguished by whether or not they express surface markers such as vimentin and nestin (38,39).…”
Section: Nscs Produce a Variant Form Of Lamininmentioning
confidence: 99%
See 1 more Smart Citation
“…In the olfactory system, astrocytic function may include tissue remodeling associated with mitosis and migration of other cells. Astrocyte production of laminin and other extracellular matrix components such as tenascin-C and chondroitin sulfate has been demonstrated under both normal and pathological conditions (29,37). To add further levels of complexity and diversity, there appear to be multiple subsets of GFAP-expressing astrocytes in the olfactory system, distinguished by whether or not they express surface markers such as vimentin and nestin (38,39).…”
Section: Nscs Produce a Variant Form Of Lamininmentioning
confidence: 99%
“…Laminin is thought to be involved in the development of the brain (28) and in the regulation of NSC migration, expansion, and differentiation into neurons and astrocytes (29). Glial cells of mammalian brain produce a variant form of laminin composed only of ␤ and ␥ chains (30).…”
Section: Nscs Produce a Variant Form Of Lamininmentioning
confidence: 99%
“…This is also where fibronectin, the other major matrix glycoprotein, occurs in brain tissue (Schachner et al, 1978;Paetau et al, 1980). Recently, we detected laminin production by rat astrocytes in primary culture (Liesi et al, 1983a) and found that in cultured neuroblastoma cells the ultrastructural localization of laminin (Liesi, 1983) is compatible with a role for this glycoprotein in cell-to-cell and cellto-substratum interactions (Terranova et al, 1980;Ekblom et al, 1980;Liesi, 1983). Brain injury is known to exert a glial reaction that involves a conversion of the protoplasmic astrocytes of the gray matter into reactive astrocytes positive for glial fibrillary acidic protein (GFAP) (Bignami and Dahl, 1974b;Bignami et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Among the matrix components, laminin has an important role as it promotes neurite outgrowth and extension of several nerve cell types (Sanes, 1989). Laminin is produced by Schwann cells and astrocytes (Liesi et al, 1983;Bunge et al, 1989) and is a basal membrane component in the peripheral nerves (Bunge et al, 1989) and in selected regions of the central nervous system (Liesi, 1985). Nerve cells recognize laminin via cell-surface receptors of the integrin family (Reichardt et al, 1989).…”
Section: Introductionmentioning
confidence: 99%